Imaging of Adrenal Masses with Emphasis on Adrenocortical Tumors - Anders Sundin (Theranostics, 2012)
Because of the more widespread and frequent use of cross-sectional techniques, mainly computed tomography (CT), an increasing number of adrenal tumors are detected as incidental findings (“incidentalomas”). These incidentaloma patients are much more frequent than those undergoing imaging because of symptoms related to adrenal disease. CT and magnetic resonance imaging (MRI) are in most patients sufficient for characterization and follow-up of the incidentaloma. In a minor portion of patients, biochemical screening reveals a functional tumor and further diagnostic work-up and therapy need to be performed according to the type of hormonal overproduction. In oncological patients, especially when the morphological imaging criteria indicate an adrenal metastasis, biopsy of the lesion should be considered after pheochromocytoma is ruled out biochemically. In the minority of patients in whom CT and MRI fail to characterize the tumor and when time is of essence, functional imaging mainly by positron emission tomography (PET) is available using various tracers. The most used PET tracer, [18F]fluoro-deoxy-glucose (18FDG), is able to differentiate benign from malignant adrenal tumors in many patients. 11C-metomidate (11C-MTO) is a more specialized PET tracer that binds to the 11-beta-hydroxylase enzyme in the adrenal cortex and thus makes it possible to differ adrenal tumors (benign adrenocortical adenoma and adrenocortical cancer) from those of non-adrenocortical origin.